Studi Tentang Makanan Adat dalam Tradisi Ayam Bulek di Nagari Tapan Kabupaten Pesisir selatan: representasi nilai sosial dan religius dalam sajian makanan adat tradisi ayam bulek di nagari tapan - Vivi Riadi, Azzahra; Kasmita; Gusnita, Wiwik; Indrayeni, Wiwik (Pasundan Food Technology Journal (PFTJ), 2025)
This research is motivated by changes in the implementation of wedding traditions in Nagari Tapan, which causes the younger generation to lack understanding of the meaning and original form of the culture. The purpose of this study is to describe the series of implementation of the Ayam Bulek tradition in Nagari Tapan, with a focus on the types of traditional foods served in the tradition. A descriptive qualitative method is used in the study with observation, interview, and documentation techniques as techniques in the research. The study has 10 informants consisting of Niniak Mamak, Bundo Kanduang, and local people who have in-depth knowledge of the traditions and traditional foods in the Ayam Bulek ceremony. The results of the study are divided into two parts consisting of general and specific findings. General findings cover the geographical and demographic conditions of Nagari Tapan, while specific findings contain the types of food served in the Ayam Bulek tradition, such as bulek chicken, ronjok/rantang, tiered cakes, accompanying cakes, and symbolic mandai containing staple foods. The main food ingredients used include rice, animal and vegetable protein sources, vegetables, flours, and other additional ingredients. The dominant seasoning used is wet seasoning, with cooking techniques including boiling, stewing, deep-frying, baking, and steaming. The dishes served in the Ayam Bulek tradition have deep symbolic and philosophical significance, reflecting the cultural values ​​and moral values ​​of the Nagari Tapan community. Therefore, this tradition is recommended for continued preservation as a local cultural heritage.